The Effect of Green Finance and Green Accounting on Manufacturing Firm Profitability in Makassar - Susi; Wa Ode Rayyani (Riset Akuntansi dan Bisnis Indonesia, 2026)
Purpose: This study aims to analyze the effects of green finance and green accounting on the profitability of manufacturing companies in Makassar during the postpandemic period. Methodology: This study employed a quantitative explanatory approach using a purposive sampling technique. Secondary data were obtained from financial reports and sustainability reports of 30 sample observations covering the period from 2021 to 2025. Data analysis was conducted using multiple linear regression with the assistance of SPSS. Results: The findings indicate that both partially and simultaneously, green finance and green accounting have a positive and significant effect on improving corporate profitability, as measured by Return on Assets (ROA). Conclusions: The implementation of transparentenvironmental governance should not be perceived merely as a cost burden but rather as a strategic approach that promotes operational efficiency and enhances financial performance, particularly in labor-intensive industries. Limitations: This study is limited to the use of Return on Assets (ROA) as a proxy for financial performance and focuses only on manufacturing companies in Makassar. Contribution: This study provides empirical evidence for stakeholders and investors that environmental commitment in the manufacturing sector can strengthen corporate legitimacy and create long-term economic value.